Person Deixis in the Film Transformer: Revenge of the Fallen - I Putu Dion Ari Saputra; I Nyoman Udayana; I Gusti Ngurah Parthama (Udayana University, 2022)
The article is entitled Person Deixis in the film Transformers: Revenge of The Fallen. The Transformer franchise is one of the most successful sci-fi robotic films around the globe. It is interesting to be an object of analysis because it is well-known and received many awards. This film contains many types of person deixis that have important value in the analysis of the film by using Levinson’s theory. The aims of this study are to identify the types of the person deixis and describe the function of each deictic marker in the film Transformer: Revenge of The Fallen. The data were taken from the film Transformer: Revenge of The Fallen. They were analyzed qualitatively based on the theory proposed by Stephen C. Levinson in pragmatic (1983). In this film, there are three types of Person deixis; First-person deixis, second-person deixis, and third-person deixis. There were three types of personal deixis found based on the utterances performed by the characters; they are first-person deixis, I, we, us, me, our, I’m. second-person deixis, you, your. Third-person deixis, they, it, he, them. All of the deixis found in this movie were presented by using an informal method that provides description and explanation.